Synthesis and Investigation of the V‐shaped Tröger′s Base Derivatives as Hole‐transporting Materials. Issue 14 (27th June 2016) - Braukyla, Titas; Sakai, Nobuya; Daskeviciene, Maryte; Jankauskas, Vygintas; Kamarauskas, Egidijus; Malinauskas, Tadas; Snaith, Henry J.; Getautis, Vytautas
Abstract: V‐shaped Tröger′s base core has been investigated as a central linking unit in the synthesis of new charge‐transporting materials for optoelectronic applications. The studied molecules have been synthesized in two steps from relatively inexpensive starting materials, and demonstrate high glass transition temperatures, good stability of the amorphous state, and comparatively high hole drift mobility (up to 0.011 cm 2 V −1 s −1 ). Abstract : V‐shaped Tröger′s base core has been investigated as a central linking unit in the synthesis of new charge‐transporting materials for optoelectronic applications. Studied molecules have been synthesized in two steps from relatively inexpensive starting materials, and demonstrate high glass transition temperatures, good stability of the amorphous state, and comparatively high hole drift mobility (up to 0.011 cm 2 V −1 s −1, see figure).